A genre analysis of university study abroad programme brochures / Lee Ee Wern - Lee, Ee Wern (2013)
Currently, tertiary education looks beyond the borders of their respective countries when considering students. Given the rising popularity of study abroad programs (Hunley, 2010; Pedersen, 2010; Asaoka & Yano, 2009; Anderson et al., 2006; Langley & Breese, 2005), which is identified in a considerable amount of existing literature that concentrates on foreign students’ experiences while studying abroad, little research exists concerning text and context analyses of the printed materials of those programs. This study focuses on the construction of information in study abroad program brochures. Utilizing Bhatia's (2004) multidimensional framework, this study examines the organizational pattern of 12 universities' study abroad program brochures within the context of Japan, Korea, China, Australia, and the United Kingdom. Concurrently, the communicative purposes, the incorporation of intertextuality and interdiscursivity, and socio-cognitive strategies in these brochures are explored. The results may help to provide explanations concerning understanding of the construction, interpretation, and usage in which study abroad program brochures are written to reach the desired target audience and also supplement universities with new information for later brochure designs.